Climate change, environmental regulations, and firms' efforts to reduce pollutant emissions - Xiao, Zehua; Cai, Cheng; Wang, Lumeng; Ma, Yigeng (Frontiers in Ecology and Evolution, 2023)
Introduction: This study investigates how climate change inspires firms to abate pollutant emissions. China is the worlds’ largest developing country. Political-based environmental regulation is an important approach to realizing environmental protection. Methods: We use data of Chinese industrial firms above a designated size from 2006 to 2013. Results: We find that climate change reduces firms’ SO2 emissions, and abatement is more evident when environmental regulation is stronger. However, firms prefer to reduce productivity and implement “end-of-pipe” intervention than engage in more green innovation. Discussion: Overall, our findings highlight how firms deal with climate change under the pressure of environmental regulation and whether ecology and economics are aligned or conflict.